Germination and mycelial growth of Bipolaris euphorbiae Muchovej & Carvalho as influenced by herbicides and surfactants - Nemoto, MCM; Nahas, E.; Pitelli, R. A.; Coelho, L. (Soc Brasileira Microbiologia, 2002)
Bipolaris euphorbiae Muchovej & Carvalho can be combined with herbicide in order to control a I large spectrum of weed species, being a strong candidate for the biocontrol of Euphorbia heterophylla L. (milk weed). The fungus release can be combined with herbicide in order to control a broader spectrum of weed species. Thus, laboratory experiments were set up to study the feasibility of using tank mixes of B. euphorbiae spores with herbicides or surfactants recommended for soybean. Mycelial growth and conidia germination were evaluated in PDA medium enriched with the herbicides oxasulfuron (80 g/ha), glyphosate (4 L/ha), bentazon (1.5 L/ha), fomesafen (1 L/ha), chlorimuron-ethyl (80 g/ha), lactofen (1 L/ha) and imazetaphyr (1 L/ha), and the surfactants Energic (2 ml/L), Aterbane (2.5 ml/L), Silwet L-77Ag (1 ml/L), Herbitensil (2 ml/L) and Natur L'oleo (10 ml/L). Dilution of the herbicides at 50% and 25% were evaluated based on solution consumption of 300 L/ha. The surfactants were evaluated only in the recommended concentrations. Mycelial growth was not affected by bentazon and fomesafen and slightly by oxasulfuron. However, glyphosate and the surfactants Energic, Herbitensil and Aterbane strongly reduced its growth. The reduction observed on imazetaphyr enriched medium was intermediate and the Natur L'oleo promoted mycelial growth. All of the surfactants allowed B. euphorbiae conidia germination equivalent to that reached in the presence of water. Energic and Herbitensil caused an expressive retardation on spore germination. The germinative process only began after 120 minutes in the presence of Herbitensil. In relation to the herbicides, it was observed that only in the presence of glyphosate and imazetaphyr the conidia germination did not follow the trend of the treatment with water.
Keywords: Bipolaris euphorbiae; mycelial growth; conidia germination; herbicides; surfactants